Webizing mobile augmented reality content - Ahn, Sangchul; Ko, Heedong; Yoo, Byounghyun (TAYLOR & FRANCIS LTD, 2014)
This paper presents a content structure for building mobile augmented reality (AR) applications in HTML5 to achieve a clean separation of the mobile AR content and the application logic for scaling as on the Web. We propose that the content structure contains the physical world as well as virtual assets for mobile AR applications as document object model (DOM) elements and that their behaviour and user interactions are controlled through DOM events by representing objects and places with a uniform resource identifier. Our content structure enables mobile AR applications to be seamlessly developed as normal HTML documents under the current Web eco-system.